The Effect of Entrepreneurial Orientation on MSMEs Development: The Mediating Role of The Utilization of Credit Facilities and Digital Marketing - Luthfiah, Lulu; Suparno, Suparno; Wibowo, Agus (Journal of Business and Economics Research (JBE), 2024)
The synergy of various components, both government and non-government institutions, policy makers, financial institution, MSMEs Actors, and other stakeholders is necessary to strive for the development of MSMEs. This research aims to examine the effect of entrepreneurial orientation and the utilization of credit facilities and digital marketing on the development of MSMEs Jakpreneur Senen District. Additionally, the mediating effects of the utilization of credit facilities and digital marketing on the relationship between entrepreneurial orientation and the development of MSMEs are also explored in this study. This research adopts a quantitative approach. The data source is primary data obtained through the distribution of questionnaires to 275 MSMEs actors in Jakpreneur, Senen District, in the food and beverage sector. Data is analyzed using Structural Equation Model (SEM) based on PLS. The research findings indicate that a significant and positive direct effect of entrepreneurial orientation on the development of Jakpreneur MSMEs in the Senen District. This is evidenced by the value of t-count 1,970 greater than t-table 1,96. The variable of credit facilities utilization has a significant and positive direct effect on the development of MSMEs Jakpreneur Senen District with t-count 3,732 greater than t-table 1,96. The variable of digital marketing utilization has a significant and positive direct effect on the development of MSMEs Jakpreneur Senen District with t-count 2,862 greater than t-table 1,96. Furthermore, there is a significant positive direct effect of entrepreneurial orientation on the utilization of credit facilities with t-count 6,720 greater than t-table. And there is a significant positive direct effect of entrepreneurial orientation on the utilization of digital marketing with t-count 5,919 greater that t-table. The study revealed an indirect effect of entrepreneurial orientation on the development of MSMEs through the mediation of credit facilities utilization. This is evidenced by the value of t-count 3,050 greater than t-table 1,96. And there is an indirect effect of entrepreneurial orientation on the development of MSMEs through the mediation of digital marketing utilization with the t value of t-count 2,365 greater than t-table.